The Effect of Social Media Marketing on Marketing Performance Mediated by Product Innovation and Ease of Use: Study on Tempe Chips Snack Entrepreneurs in Sanan, Malang Using WhatsApp - Fitria Musyarofah, Fitria Musyarofah; Fuadi, Muhammad Ilzam Nadzif Fuadi; Hadiyati , Ernani (Proceeding Economy of Asia International Conference, 2026)
Introduction/Main Objectives: This study examines how social media marketing influences marketing performance among tempe chips snack entrepreneurs in Sanan, Malang, who utilize WhatsApp, with product innovation and ease of use as mediating variables. In the digital era, social media has transformed MSME marketing from conventional face to face to efficient screen to face interactions, enabling wider market reach with minimal costs. Background Problems: Despite social media’s popularity, limited research explores its mediated effects on MSME marketing performance through product innovation and ease of use what specific relationships exist between these variables among WhatsApp using tempe chips entrepreneurs? Research Methods: Quantitative approach using Structural Equation Modeling (SEM) Partial Least Squares (PLS) with SmartPLS 4.0. Data collected via Likert scale questionnaires from 70 respondents out of 400 population (17.5% sample per Arikunto, 2019), comprising primary (surveys) and secondary data (literature). Outer/inner model tests assessed validity, reliability, and hypotheses. Finding/Results: Social Media Marketing significantly affects product innovation (T=61.112, p=0.000), ease of use (T=40.576, p=0.000), and marketing performance (T=2.695, p=0.007). Product innovation positively impacts marketing performance (T=3.335, p=0.001) and mediates the relationship (T=3.314, p=0.001), while ease of use shows no significant effect (T=0.521, p=0.602) or mediation. All R²>0.87 (high explanatory power); Q²>0.87 (high predictive relevance). Conclusion: Social Media Marketing boosts MSME marketing performance primarily through product innovation, not ease of use. Entrepreneurs should integrate WhatsApp strategies with continuous innovation for sustained competitiveness; future research could expand samples and variables.